Effect of occlusal plane correction on lip cant in two-jaw orthognathic surgery - a three-dimensional analysis - Freudlsperger, Christian; Rückschloß, Thomas; Ristow, Oliver; Bodem, Jens; Kargus, Steffen; Seeberger, Robin; Engel, Michael; Hoffmann, Jürgen; Mertens, Christian (Journal of cranio-maxillofacial surgery, 2017)
Introduction: The aim of the present study was to evaluate the impact of canting correction in occlusal plane (OP) on the change of lip cant (LC) using three-dimensional (3D) photogrammetry in combination with cone-beam computed tomographic (CBCT) scans in class III asymmetric patients. Materials and methods: Fourteen asymmetric patients with exclusively skeletal class III malocclusion undergoing two-jaw surgery were included. All patients received 3D-photogrammetry and CBCT scans before (T1) and after orthognathic surgery (T2). After image fusion of the CBCT scans, angular correction of the occlusal plane (COP) between T1 and T2 was measured. Accordingly, angular correction of the lip cant (CLC) was analyzed after matching the preoperative 3D-photogrammetric scan to the postoperative. Results: At the T1 stage, the canting of the OP was higher compared to the LC (4.95° vs. 3.77°). During T1 to T2, a significant angular cant correction was observed: COP (2.64°, p = 0.004) and CLC (1.76°, p = 0.01). In addition, a linear relationship between COP and CLC was revealed with a correlation coefficient for angular change of 0.47. For the linear regression COP turned out to be a predictor for CLC (B = 0.372, t (13) = 1.848, p = 0.089). Hence a correction of the OP of 1° resulted in a correction of the LC of only 0.372°. Discussion: The use of CBCT scans in combination with 3D-photogrammetry are valuable tools to accurate analyze canting corrections of the OP and the LC during orthognathic surgery.
Gesehen am 04.05.2018